The impact of the endowment on photovoltaic energy to support Palestinian university education: A maqasid jurisprudential View - Assaf, Mohammad Motlaq; Khaseeb, Mohammad Saied (Journal of Islamic Sciences, 2021)
This study aims at providing the influence of the endowment on solar energy. And its reflection on the scientific university life. Also it aims at supporting the university education in Palestine by supporting new ideas to support the scientific research's by clarifying the legal texts, according to university situations to reduce deficit value in Palestinian universities. The electrical energy is considered the main columns of the environmental and civilization progress. As it's mainly connected to the instruments and equipment that make life easier. These instruments burn fuel that leads to harmful and dangerous effects on environment. During scientific research'. scientists found out that they can convert solar energy into Photovoltaic energy that doesn't need to burn fuel to be generated. This saves money as well as building new cultures to help in modernising the world. The abstract reach's to great likeness of the use of the endowment to serve the generated solar system. It's mainly a good application for the Islamic legal services on a solid ground. And it's related to environment protection and to saving money. So the legal endowment is able to solve problems of the continuous increasing cost of traditional power components.
Keywords: Endowment; photovoltaic energy; University education; the Preservation of the environment; money saving purpose